Soybean Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2009)
This publication contains information for a projected budged reflecting expected income and cost based on soybean production practices in western Kansas.
MF2366_2009_12
Keywords: MF2366; Economics; Crops; MF